Exploring the needs and coping strategies of New Zealand parents in the neonatal environment. (17th February 2022) - Dodge, Andrew; Gibson, Charlotte; Williams, Matt; Ross, Kirsty
Abstract : Aim: Having an infant admitted to a neonatal care facility can be highly distressing for parents given the fragile state of their child and the often‐unfamiliar environment. This study aimed to explore the needs and coping strategies of parents in this setting. Methods: An online qualitative survey was used to explore the needs of parents who had a child discharged from a New Zealand neonatal unit in the past 12 months. A total of 394 parents participated in the study (387 mothers, 5 fathers), providing 970 responses across three open‐ended questions examining their needs, unmet needs and coping strategies. The study included participants across both neonatal intensive care units and special care baby units, with prematurity (47%) the most common reason for admission. An inductive form of thematic analysis was used to analyse the data. Results: Four themes were developed that capture the needs and coping strategies expressed by parents in this study: communication and information; physical contact and access to the baby; emotional and non‐medical support; and involvement, autonomy and respect. Conclusions: The themes developed largely centre around the struggle parents face when confronting the uncertainty of the neonatal environment and the difficulty in establishing their parental role. Parental distress may be reduced through communicating accurate information regularly and providing empathetic understanding, while opportunities for physical contact and involvement may assist in raising parental confidence and scaffolding the journey to independent care of their infant.